Knowledge and attitude of pregnant women at risk for having a fetus with severe thalassemia after genetic counseling at Srinagarind Hospital - Surangrhut Pauisri; Piyamas Saksiriwuttho; Thawalwong Ratanasiri (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objectives: The primary objective was to assess the knowledge and attitude of pregnant women at risk for having a fetus with severe thalassemia after receiving genetic counseling from Maternal and Fetal Medicine Staffs at Srinagarind Hospital and the secondary objective was to analyze the factors associated with decision of prenatal diagnosis and termination of pregnancy.Materials and Methods: Descriptive study recruited 105 pregnant women who were at risk for having a fetus with severe thalassemia after genetic counseling during September 1, 2010 to January 31, 2011. The questionnaire consisted of four parts demographic characteristics, knowledge of thalassemia, attitude towards thalassemia and factors associated with decision of prenatal diagnosis and termination of pregnancy after genetic counseling. Data analysis was done by using descriptive statistics, chi-square test and odds ratio.Results: More than half of the participants (57.1%) had adequate knowledge of thalassemia. The three significant contributing factors of thalassemia knowledge were education level (bachelor degree) (OR 33.4, 95% CI 3.6-310.3), family income (more than 20,000 Baht/month) (OR 6.4, 95% CI 1.5-27.1) and desire to have children (unplanned pregnancy) (OR 0.3, 95% CI 0.13-0.82), (p<0.05). Most of participants (85.7%) had good attitudes towards thalassemia. Ninety five percents of participants decided to have prenatal diagnosis of thalassemia when indicated and 88.0% of those accepted to terminate pregnancy if the fetuses were affected. Conclusion: Knowledge and attitude of thalassemia in pregnant women at risk were adequate and good. Factors associated with decision of prenatal diagnosis and termination of pregnancy probably were education level, family outcome and desire to have children.